ПЕДАГОГИК ИМИЖНИ ШАКЛЛАНТИРУВЧИ ОМИЛЛАР - Бобожонов, Ф.Қ. (SCIENCE and SOCIETY, 2019)
The article is devoted to the issues of forming the factors of pedagogical image and its role in the educational process.